(untitled) (Research, Society and Development, 2022)
The olive tree (Olea europaea L.) is a fruit-bearing plant, native to tropical and temperate regions and one of the oldest cultivated. The use of plant extracts with known antimicrobial activity can acquire meaning in therapeutic treatments. The objective of this work is to evaluate the antifungal activity of residues from the olive industry (bagasse) in the Picual variety and of vegetative parts of olive cultivars (Olea europaea L.) of the Arbequina and Picual varieties, against Candida spp., Microsporum gypseum and Sporothrix brasiliensis. The methodology for the in vitro tests was referenced by the document M27-A3 recommended by the CLSI for yeasts and M38-A2 for filamentous fungi, adapted for the use of phytotherapics. The antifungal activity of the hydroalcoholic extracts of leaves of Olea europaea L. stood out in the final result, presenting inhibitory action at concentrations of 50 mg/ml, 100 mg/ml and 200 mg/ml, followed by the aqueous decoction extract at the same concentrations. The hydroalcoholic extracts of the bagasse of the Picual variety and the leaves of the Picual and Arbequina varieties showed promising fungistatic activity against the isolates of Microsporum gypseum, with CIM ranging from 100 mg/ml to 200 mg/ml. The results demonstrate the potential of these extracts in the treatment of dermatophytosis, but more studies should be carried out against other species of dermatophytes to prove their effectiveness, in addition to cytotoxicity tests. The infusion and hydroalcoholic extracts from the leaves of the Picual variety showed greater inhibitory action against Candida spp. and Sporothrix brasiliensis presenting important parameters to point out the products as a therapeutic alternative.